2021
DOI: 10.1002/lary.29910
|View full text |Cite
|
Sign up to set email alerts
|

HPV‐Positive Status Is an Independent Factor Associated With Sinonasal Inverted Papilloma Recurrence

Abstract: Objectives: The present study aimed to evaluate human papillomavirus (HPV) occurrence in sinonasal inverted papilloma (SNIP), and to assess factors associated with HPV positivity and SNIP recurrence.Study Design: Prospective study. Methods: We prospectively collected clinical data and fresh tissue specimens from 90 consecutive patients treated for SNIP at Helsinki University Hospital, between 2015 and 2019. Fourteen patients with recurrent SNIP underwent repeated tumor sampling. All tissue specimens were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Identification of the IP attachment site is vital for preventing the recurrence. Most of scholars reported that the attachment site may be accurately identified [ 11 , 22 ]. In this study, although 28.9% had the history of previous surgery, MMA alone or Caldwell-Luc approach alone was performed in initial surgery, the attachment site hadn’t been eradicated, thus, the IP attachment sites were identified in all the patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Identification of the IP attachment site is vital for preventing the recurrence. Most of scholars reported that the attachment site may be accurately identified [ 11 , 22 ]. In this study, although 28.9% had the history of previous surgery, MMA alone or Caldwell-Luc approach alone was performed in initial surgery, the attachment site hadn’t been eradicated, thus, the IP attachment sites were identified in all the patients.…”
Section: Discussionmentioning
confidence: 99%
“…The preferred treatment for IP is minimally invasive, attachment-oriented endoscopic surgery. This surgery includes the identification of the tumor attachment site, a subperiosteal dissection, and a resection or drilling of the underlying bone [ 1 , 10 , 11 ]. Despite the theoretical advantage of subperiosteal dissection and bone drill, these techniques have still shown high tumor recurrence rates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the difference between stages T1 and T2, and also between T3 and T4, is insignificant 2 . A higher prevalence of HPV infection, and also increased risk for SNIP recurrence have been observed in smokers 3,4 . The risk for SNIP recurrence may also depend on surgical technique.…”
Section: Introductionmentioning
confidence: 99%